Oxidative stress in amyotrophic lateral sclerosis (ALS) 1 - Shaw, Pamela (Henry Stewart Talks, 2022)
Introduction to Amyotrophic Lateral Sclerosis (ALS)/Motor Neuron Disease (MND), Clinical genetic and pathological heterogeneity of MND, Mechanisms of neuronal oxidative stress, Mitochondria oxidative stress response, Antioxidant defence mechanisms, Evidence for the role of oxidative stress in SOD1 MND, The role of Nrf2 in MND